2020
DOI: 10.1097/md.0000000000022070
|View full text |Cite
|
Sign up to set email alerts
|

What is the optimal regimen for intravenous dexamethasone administration in primary total hip arthroplasty?

Abstract: Background: A number of recent studies have investigated the optimal dosage and timing of dexamethasone in total hip arthroplasty (THA) but have inconsistent findings. Therefore, we designed the randomized controlled research to look for the optimal intravenous dexamethasone dose for the treatment of early postoperative pain after the THA. Methods: The Declaration of Helsinki principles was followed and the Consolidated Standards of Reporting Trials guidelines for rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…The result showed that not only could statistically reduce the incidence of PONV P 0.05 , but serious complications, such as hyperglycemia, periprosthetic joint infection PJI and gastrointestinal hemorrhage had no signi cant difference compared to the other, and there was no statistical difference P 0.05 .They con rmed the application of dexamethasone in the perioperative period of THA was safe and effective, at the same time, suggested that there should be further promoted its application in joint replacement. In our study, the incidence of poor wound healing was 6.0% (3/50) in the dexa group and 8.33% (4/48) in the placebo group, and there was no statistically signi cant difference (P=0.66).No serious complications such as incision infection or gastrointestinal hemorrhage were found in all patients, which also con rmed the safety of two low-dose dexamethasone applications in the perioperative period of THA, and that was consistent with the results of previous studies [4,10,16] .However, it should be pointed out that some…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The result showed that not only could statistically reduce the incidence of PONV P 0.05 , but serious complications, such as hyperglycemia, periprosthetic joint infection PJI and gastrointestinal hemorrhage had no signi cant difference compared to the other, and there was no statistical difference P 0.05 .They con rmed the application of dexamethasone in the perioperative period of THA was safe and effective, at the same time, suggested that there should be further promoted its application in joint replacement. In our study, the incidence of poor wound healing was 6.0% (3/50) in the dexa group and 8.33% (4/48) in the placebo group, and there was no statistically signi cant difference (P=0.66).No serious complications such as incision infection or gastrointestinal hemorrhage were found in all patients, which also con rmed the safety of two low-dose dexamethasone applications in the perioperative period of THA, and that was consistent with the results of previous studies [4,10,16] .However, it should be pointed out that some…”
Section: Discussionsupporting
confidence: 90%
“…Total hip arthroplasty (THA) is one of the most effective treatment for the end-stage hip diseases, which can greatly improve the mobility and quality of life of patients [1] .However, surgical trauma often causes severe postoperative in ammation during THA, which may lead to increased postoperative pain and fatigue, increased incidence of postoperative nausea and vomiting (PONV), prolonged hospital stays, and slowed down early recovery speed.As a consequence, that may indirectly reduce patient satisfaction [2] .Therefore, it is of great signi cance to actively control perioperative in ammation of THA, reduce pain, fatigue, nausea and vomiting.Glucocorticoids, a class of steroid hormones with considerable anti-in ammatory effects, have been widely used in many surgical elds including THA [3,4] .But the use of dexamethasone during the perioperative period of THA has slowed the pace due to concerns about adverse reactions.In recent years, some studies have reported that glucocorticoids can reduce PONV and fatigue, and are also recommended as part of THA multi-mode analgesia programs [5][6][7] . However, due to clinical heterogeneity, the optimal time, mode and dose of glucocorticoids in THA has not been determined, which may lead to signi cant differences in clinical outcomes.Although side effects are relatively low, most regiments are still given in a single low-dose intravenous administration [8,9] .…”
Section: Introductionmentioning
confidence: 99%